PIV-PTV measurements of water and sediment flows - Aleixo, Rui (2019)
In the domain of fluvial hydraulics, it is critical to know the velocity field of both solid and liquid phases (sediments and water). From the velocity field it is possible to determine different variables such as shear stresses, identify recirculation regions, among others. The development of optical techniques allowed for measurement techniques based on image acquisition and processing, namely PIV (particle image velocimetry) and PTV (particle tracking velocimetry). In this paper an algorithm combining both PIV and PTV techniques is presented, allowing in this way to profit from each technique strong points and allowing the simultaneous measurement of the water and sediment layer velocity fields and to obtain a better know how of the fluid-sediment interaction. The advantages and limitations of the proposed techniques are explored and debated by means of a laboratory experiment.